Debt Management: Payment of Residential Property Rates in a Selected District Municipality in South Africa - Enwereji, Prince Chukwuneme; Kadama, Frazer (International Journal of Economics and Financial Issues, 2018)
Payment of residential property rates continues to be a contentious issue among the leaseholders in South Africa. The study investigates the payment practices on residential properties in one municipality. The purpose of the study was to identify the causes of defaults in payment of rates and to proffer solutions to minimise defaults and to recover debts. Systems and contingency theories underpinned the study. A mixed method approach involving both qualitative and quantitative data was applied. The population comprised of five local municipalities, 185 268 residential leaseholders and 437 municipal workers. Data were collected using questionnaires and semi-structured interviews. Survey data were analysed using Statistical Package for the Social Science while data collected from the interviews were transcribed, coded and discussed. The study concluded that defaults in payment were, inter alia, caused by failure of municipalities to impress upon residents the importance of paying rates and to promote alternative payment options. Keywords: Debt Management, Communication, Municipal Financial Administration JEL Classifications: D83, H63